(untitled) - Malashree; Vinod M (Academia Anesthesiologica International, 2019)
Background: Bupivacaine hydrochloride is a white, odourless, crystalline powder with a bitter, numbing taste. It is prepared by chemical synthesis. The hydrochloride salt is available in solution with and without epinephrine. A preparation marketed specifically for intrathecal use contains dextrose.Subjects and Methods: Data was collected from 90 patients in the age group of 30-60 years of ASA class I & II, posted for elective TAH without any co-morbid diseases were grouped randomly by using closed sealed opaque envelope technique. The study drug was prepared by an anesthesiologist, who was not involved with the study. All spinal blocks were given by the same anesthesiologist who also was the observer. Results: 4 patients in Dexmedetomidine group, 2 patients each in Fentanyl group and control group developed bradycardia which was managed by Inj. Atropine 0.6 mg IV. 11 patients in Dexmedetomidine group, 7 patients in Fentanyl group and 4 patients in control group developed hypotension which was managed by Inj. Mephenteramine 6mg IVincremental doses. 1 patient in Group-F developed vomiting which was managed by Inj. Ondonsetron 4mg IV. Conclusion: In our study there was no statistically significant difference in the adverse effects throughout the procedure when Group-D and Group-F were compared with group-B and also there was no statistically significant difference when Group-D was compared with Group-F.